A computational insight on self - etchinh and bistyrenic monomers - Özaydın, Gül Beste. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Cyclopolymerization reaction of difunctional styrene monomers and the efficient binding of self-etching monomers to the hydroxyapatite component of the tooth have been widely studied using empirical approaches. However, the literature lacks a relevant computational basis to supplement such findings. Therefore, this thesis aims at bringing a computational insight into the i) cyclopolymerization reaction of difunctional styrenic monomers and ii) self-etching monomers in dental applications. In the first part of this work, the synthesis and the efficient cyclopolymerization of difunctional monomers containing styrene moieties tethered each other by the dichlorodiphenylsilane, the dichloro(methyl)phenylsilane and malonate ester protecting groups are illustrated. The experimental findings are rationalized theoretically by tackling the initial steps of cyclopolymerization reaction such as initiation, cyclization, propagation. In the second part, self-etching monomers and pre-nucleation complexes are modeled by computational protocols. These monomers are of interest in the dental adhesive system applications due to their strong binding to the hydroxyapatite component of the tooth. In order to analyze the strength of the interaction between calcium (HAP) and acid groups (selfetching monomer), pre-nucleation complexes (PNC), have been considered. The interaction between monomers and pre-nucleation complex is examined by the calculation of dissociation energy and the evaluation of NPA charges for PNC-monomer complexes. The computational findings have supported the experimental stability order of the monomers, The computational approach enables the scope of the evaluation of newly designed monomers to be wide in a short period of time without high experimental cost.
Keywords: Monomers.